Business takeovers and firm growth: Empirical evidence from a German panel - Harald Habermann (Institut für Mittelstandsforschung (IfM) Bonn, 2017)
The present article links business takeovers to the literature on serial autocorrelation of growth rates. The aim of the study is to identify the effects of successions on the performance of small German firms by analysing the growth pathways over a period of eight years after business takeover. Using panel data from 1,872 firms, the present article shows that for the first two years after a business takeover, small firms are subject to negative serial correlation of growth rates regarding employment. The analysis underlines the importance of longitudinal data to provide evidence on changes in the behaviour of a firm following a business takeover. – – Der vorliegende Artikel verbindet Geschäftsübernahmen mit der Literatur über die serielle Autokorrelation von Wachstumsraten. Ziel der Studie ist es, die Auswirkungen von Nachfolgen auf die Leistungsfähigkeit kleiner deutscher Unternehmen über einen Zeitraum von acht Jahren nach der Unternehmensübernahme zu analysieren. Mit Hilfe von Panel-Daten von 1.872 Firmen zeigt der vorliegende Artikel, dass kleine Unternehmungen für die ersten zwei Jahre nach einer Übernahme einer negativen seriellen Korrelation der Wachstumsraten, gemessen anhand der Beschäftigung, unterliegen. Die Analyse unterstreicht die Bedeutung von Längsschnittdaten, um Veränderungen eines Unternehmens nach einer Übernahme zu untersuchen.
Keywords: L25; M13; M21; 330; business takeovers; successions; autocorrelation; panel data; small firms